Maltrato psicológico y aprendizaje de los estudiantes de la Unidad Educativa “Alfredo Pérez Guerrero” Guano, Chimborazo. Periodo Noviembre 2020 – Abril 2021 - Melena Cajamarca, María Belén (2021)
This research was carried out through a quantitative approach, which arose from identifying psychological abuse through the application of a survey and aimed to analyze the relationship between psychological abuse and learning from General Basic Education (EGB) students from the "Alfredo Pérez Guerrero" Educational Institution. Psychological abuse is the emotional damage caused to a person, affecting their self-esteem and the ability to relate to others and achieve the expected learning. Children who suffer from psychological abuse lack development in their personality, behavior, and school performance. That is why these two variables have been investigated. They allowed us to show that some students were going through this problem. From the methodological perspective, non-experimental, correlational field research was carried out by objectives, basic and transversal time. The sample was intentionally non-probabilistic and was made up of EGB students from the "Alfredo Pérez Guerrero" Educational Unit. The techniques used for the independent variable such as psychological abuse, a survey. Likewise, for the dependent variable, learning the evaluation with its particular instruments: a questionnaire and report cards. The results indicate a negative and inverse correlation between the variables; that is, the higher the level of one, the lower the level of the other, and vice versa.